A teaching case study of the strategic alignment of business strategy and information technology strategy at Nedbank - Tsoaeli, Tebalo (Rhodes University, Faculty of Commerce, Rhodes Business School, 2013)
In today's business world, a lot of organizations are investing heavily in Information Technology (IT) in order to develop a competitive edge. According to Loukis, Sapounas and Milionis (2009:85) "firms all over the world make significant investments in IT aiming to increase their efficiency and effectiveness" . According to Cline and Guynes (2001:10), "during the last 30 years, IT has become an increasingly integral part of business operations" . Most of the times, organizations fail to get real value from the investments made in IT. This is mainly due to the fact that organizations fail to realize the value brought about by aligning IT strategy with Business strategy. Hu and Huang (2004:60) state that "each year organizations invest in IT to improve their competitive advantage and ultimately their business performance; however, more often than not, the anticipated benefits of IT investments fail to materialize due to misalignment of or lack of alignment, between the business and IT strategies" . Henderson and Venkatraman (1999:475) emphasize that "alignment is a desired state for organizations investing in IT that is not always achieved, as it often entails a radical change in the way managers consider IT" . It is through the alignment of IT strategy and Business strategy that organizations are able to realize the value brought about by investing in IT. Papp (2001:20)illustrates that "misalignment can cause problems with not only the development and integration of business and IT strategies, but can actually prevent IT from being fully leveraged to its maximum potential within an organization" . An organization that realizes the value of aligning IT strategy and Business strategy is able to develop a competitive advantage over its competitors. According to Daneshvar and Ramesh (2010:1) "each organization is aware of the special effects, benefits and implication of IT in business performance and also its capacity in building sustainable competitive advantages" .
Keywords: Nedbank; Banks and banking -- South Africa; Business planning; Information technology